Novel benzimidazole derivatives: Cytotoxic and apoptotic properties on lung cancer cell line - Yurttaş, Leyla; Akalın Çiftçi, Gülşen; Aksoy, Mehmet Onur; Demirayak, Şeref (Bentham Science Publishers, 2020)
Background: Benzimidazole derivatives are privileged molecules known to have a wide variety of biological activities. In medicinal chemistry, due to the ring's structural similarity to nucleotides, its derivatives were investigated as new chemotherapeutic agents. Our research group have been studying 1,2-disubstituted benzimidazoles, including thiocarbamoyl group and their potential anticancer activity. Based on previous findings, we synthesized novel 1-[2-(4-substituted phenyl-2-oxoethyl)]-2-[(2/3/4-substituted phenylpiperidin-1-yl)thiocarbamoyl]benzimidazole derivatives (3a-o).Methods: The obtained fifteen derivatives were studied on A549 adenocarcinomic human alveolar basal epithelial cell line and mouse L929 fibroblastic cell line to determine their cytotoxic activity. These compounds were also investigated to identify their apoptotic properties.Results and Discussion: The structures of the compounds based on three different groups differ from each other with the phenyl substituents bonded to the piperazine ring. All of the compounds showed remarkable antitumor activity, but the first five compounds bearing non-substituted phenyl moiety exhibited selective cytotoxicity when compared in terms of potencies to the normal cell line.Conclusion: Compounds 3j, 3m and 3n were identified as the most apoptotic derivatives; however, compounds 3e and 3h provoked apoptosis with the percentages of 10.6 and 10.9% and selective cytotoxicity.
Keywords: Benzimidazole; Piperazine; Anticancer Activity; A549 Lung Cancer; Cytotoxicity; Apoptosis